2017
DOI: 10.2533/chimia.2017.596
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Arene-forming Aldol Condensation: Stereoselective Synthesis of Rotationally Restricted Aromatic Compounds

Abstract: By taking inspiration from the fascinating biosynthetic machinery that creates aromatic polyketides, our group investigates analogous reactions catalyzed by small molecules. We are particularly captivated by the prospects of intramolecular aldol condensation reactions to generate different rotationally restricted aromatic compounds. In a first project of our independent research group, a highly stereoselective amine catalyzed synthesis of axially chiral biaryls, tertiary aromatic amides and oligo-1,2-naphthyle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Our previous efforts were engaged in polyketide cyclizations of artificial aldehyde substrates with pre‐organizing aromatic moieties . The mild substrate preparation and the observed control over increasingly complex substrates thereby indicated the feasibility of small‐molecule catalyzed, divergent cyclizations of native polyketides, if the reactivity and selectivity requirements are met.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous efforts were engaged in polyketide cyclizations of artificial aldehyde substrates with pre‐organizing aromatic moieties . The mild substrate preparation and the observed control over increasingly complex substrates thereby indicated the feasibility of small‐molecule catalyzed, divergent cyclizations of native polyketides, if the reactivity and selectivity requirements are met.…”
Section: Methodsmentioning
confidence: 99%
“…Our group focused on the development of atroposelective areneforming aldol condensations, which were inspired by the biosynthesis of aromatic polyketides. [44,45] The amine catalyzed aldol methodology was found to be broadly applicable permitting the preparation of binaphthalene carbaldehydes, [46] configurationally stable oligo-1,2-naphthylenes [47] , axially chiral amides [48] and the stereodivergent synthesis of atropisomeric multi-axis systems. [49]…”
Section: Stereoselective Synthesis Of Atropisomersmentioning
confidence: 99%
“…These cyclization studies [44][45][46][47][48][49] revealed the ability of smallmolecule catalysts to trigger polyketide-type cyclizations and suggested that also noncanonical polyketide cyclizations, that are related to the conversion of poly-β-carbonyl compounds by the polyketide synthase machineries, could be feasible. of substrates to examine this hypothesis involved the preparation of cinnamyl biindene precursors which were accessed through an oxidative dimerization or a Suzuki crosscoupling strategy.…”
Section: Synthesis Of Enantioenriched Tetra-ortho-33'-substituted Bimentioning
confidence: 99%
“…However, although the enantioselective and diastereoselective aldol reactions have been developed significantly, the atroposelective versions of them are rare . The Sparr group performed atroposelective arene-forming aldol reactions using proline-driven organocatalysts and further used them elegantly in some natural products and axially chiral amide syntheses . Here, we report atroposelective aldol reactions of axially chiral thiohydantoin derivatives using a different approach.…”
Section: Introductionmentioning
confidence: 99%